4(x+5)=3(x-11)

Simple and best practice solution for 4(x+5)=3(x-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+5)=3(x-11) equation:


Simplifying
4(x + 5) = 3(x + -11)

Reorder the terms:
4(5 + x) = 3(x + -11)
(5 * 4 + x * 4) = 3(x + -11)
(20 + 4x) = 3(x + -11)

Reorder the terms:
20 + 4x = 3(-11 + x)
20 + 4x = (-11 * 3 + x * 3)
20 + 4x = (-33 + 3x)

Solving
20 + 4x = -33 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
20 + 4x + -3x = -33 + 3x + -3x

Combine like terms: 4x + -3x = 1x
20 + 1x = -33 + 3x + -3x

Combine like terms: 3x + -3x = 0
20 + 1x = -33 + 0
20 + 1x = -33

Add '-20' to each side of the equation.
20 + -20 + 1x = -33 + -20

Combine like terms: 20 + -20 = 0
0 + 1x = -33 + -20
1x = -33 + -20

Combine like terms: -33 + -20 = -53
1x = -53

Divide each side by '1'.
x = -53

Simplifying
x = -53

See similar equations:

| (5h+2)=-8 | | 3g-8=-2+2g-10 | | 25=x-16 | | -3h+12=-7h-9-16 | | 9(x-14)=35-7(x+5) | | 24x•35y/25x | | (b+9)=2 | | 14.4=-2.7x-1.8 | | 7p-10=9p+6 | | (3z-3)=9 | | 1.4x-5.6=2.8 | | ax-ab=bx | | 5u=7+6u | | 15-x-9=21 | | 2=11+3a | | 7d-10=8(d-3) | | 4(x+3)=-6(7+5x)+34x | | -8d=5-7d | | 45=-25+32x | | -b=-2b+4 | | 4(w-3)=-9w-38 | | 400-16u=15u+18+6 | | -4+3w=-7+6w | | F(5)=6 | | 10-3b+3=-1 | | 27x+8=20 | | 25n+0.08(25m)+17= | | F(5)=7 | | 62x-14-8x=16+54x-30 | | 3/4x-2/7=1/4 | | 5n-7=-2n | | X=1.1+2.7 |

Equations solver categories